Features shaped structure prose R. Seysenbaev (Eurasian Journal of Philology Science and Education, 2015)
This article discusses one of the features of creating characters in philosophical prose R. Seysenbaeva, which is based on the principle of duality . Phenomenon of duality has different interpretations , depending on whether it is given in the epic work or a classic novel. In the novel "Dead wandering in the desert," we see two types of duality – and an epic novel . Duplicity novel, where the characters as opposed to "double – antagonists" embodied in the images of People and mullahs Kaiyr whose relationships are organized as confrontation and back to the mythological structure of " cultural hero – a trickster ." Also the analysis of other types of duality – the epic. This type is associated with overlapping characters. Such is the nature of construction and characters – Nasir – Kaharman- Berish. There used mythological principle in which " a lot of characters that make up the chain " should be regarded as a dis – one person.Epic duplicity due archaic consciousness, and " is the epitome of the finished mythological epic unity of the world” Epic duplicity – is, in fact, a change in the identity of the form content. In the novel, the writer, we see both the principle of creating characters .
Keywords: principle of duality; myth; archetype; cultural hero; trickster